2016
DOI: 10.1080/10463283.2016.1249640
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in repeated interactions: A systematic review of Centipede game experiments, 1992–2016

Abstract: Cooperation is a fundamental form of social interaction, and turn-taking reciprocity one of its most familiar manifestations. The Centipede game provides a formal model of such alternating reciprocal cooperation, but a backward induction argument appears to prove logically that instrumentally rational players would never cooperate in this way. A systematic review of experimental research reveals that human decision makers cooperate frequently in this game, except under certain extreme conditions. Several task,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 84 publications
0
40
0
Order By: Relevance
“…This prediction is broadly con…rmed by the available experimental evidence, (for a survey see Krokow, Colman, and Pulford (2016)). …”
Section: Experimental Papersmentioning
confidence: 60%
See 2 more Smart Citations
“…This prediction is broadly con…rmed by the available experimental evidence, (for a survey see Krokow, Colman, and Pulford (2016)). …”
Section: Experimental Papersmentioning
confidence: 60%
“…17 The centipede game was introduced by Rosenthal (1981) and studied in laboratory experiments by McKelvey and Palfrey (1992). A survey of subsequent experimental research can be found in Krokow, Colman, and Pulford (2016).…”
Section: The Centipede Gamementioning
confidence: 99%
See 1 more Smart Citation
“…Krockow, Colman, and Pulford () highlight that different explanations have been suggested to rationalize the deviations from the game‐theoretic solution and classifies them to two broad categories: insufficient cognitive ability to perform backward induction reasoning and other‐regarding motives that interfere with rational, selfish decision‐making. In a systematic review of centipede game experiments, Krockow, Colman, and Pulford () conclude by summarizing the potential reasons why players cooperate and do not follow the rational prescription of backward induction reasoning. They include four explanations: (1) the hidden assumption explanation that expectations about co‐players' future actions are unaffected by observations of their past actions; (2) the cognitive burden explanation based on the idea that backward induction is cognitively taxing and therefore players do not realize that defecting at an earlier stage may be more beneficial; (3) the common knowledge breakdown explanation, where players do not expect their co‐players to be fully rational; and (4) the other regarding preferences explanation.…”
Section: Introductionmentioning
confidence: 99%
“…We do not aim to provide a thorough review of the literature given that there exist excellent recent reviews of the experimental literature (see Krockow, Colman, and Pulford and Dhami , chapter 12, p. 729).…”
mentioning
confidence: 99%